REVIEW ON DEVELOPMENT IN FINANCIAL DISTRESS MODELING - Gillani , Syed Muhammad Ahmad Hassan; Gillani , Syed Muhammad Ahmad Hassan; Raza, Hamad; Ramakrishnan, Suresh; Gillani , Syed Muhammad Afraz Hassan; Ahmad, Humara (International Journal of Psychosocial Rehabilitation, 2020)
Financial distress is an important but undesired event of company life. If the company does not take necessary action to avoiding financial distress, then it can lead company towards bankruptcy and business windup. In past there are several studies have been carried out to figure out that what are main causes which lead companies into financial distress and eventually become bankrupt. Since 1966 till present there are several researchers investigated the causes of financial distress and developed several prediction models. This study included only those studies, which significantly contributed in the literature of financial distress. Moreover, Selected studies highlighted new variable and opted new statistical techniques.